Chiral Auxiliary Induced Diastereoselective Synthesis of (R, R)‐N, N′‐Di(tert‐butoxycarbonyl)cyclohex‐4‐ene‐1, 2‐diamine. Issue 36 (21st November 2014) - Balestri, Davide; Grilli, Stefano; Romano, Ciro; Savoia, Diego
Abstract: The synthesis of optically pure N, N′ ‐di( tert ‐butoxycarbonyl)‐ trans ‐cyclohex‐4‐ene‐1, 2‐diamine was accomplished from the diimine, which was obtained by condensation of glyoxal and ( R )‐1‐(4‐methoxyphenyl)ethanamine. The synthetic sequence involved the highly diastereoselective addition of allylzinc bromide to the diimine to give the N, N′ ‐disubstituted octa‐1, 7‐diene‐4, 5‐diamine, followed by removal of the N‐substituents by using an excess amount of boron trichloride, routine conversion to the di( N ‐ tert ‐butoxycarbonyl) derivative, and final ring‐closing metathesis by using Grubbs Ru catalyst. The sequence of the two latter steps could be inverted. Removal of the chiral auxiliaries with trifluoroacetic acid or hydrochloric acid gave less satisfactory results. Moreover, N, N′ ‐dibenzoylocta‐1, 7‐diene‐4, 5‐diamine was similarly prepared. Abstract : ( R, R )‐ N, N′ ‐Di( tert ‐butoxycarbonyl)cyclohex‐4‐ene‐1, 2‐diamine is synthesized from the glyoxal diimine, which is prepared by using a chiral auxiliary. Double allylation to the diimine proceeds with excellent diastereoselectivity; then, removal of the N‐substituents followed by ring‐closing metathesis (RCM) of the diene moiety affords the protected cyclohex‐4‐ene‐1, 3‐diamine in satisfactory overall yield.